Beliefs About Evolution and Educational Attainment1. Issue 4 (30th July 2018) - Longest, Kyle C.; Uecker, Jeremy E.
Abstract : Using panel data from the National Study of Youth and Religion, we examine the effect of beliefs about evolution in high school on several postsecondary educational outcomes. Results indicate that net of a host of background factors and potential alternative explanatory factors, there are significant associations between beliefs about evolution and pursuing or obtaining a bachelor's degree, such that pure creationists (i.e., creationists who do not allow for the possibility that God used evolution to create the world) are less likely than naturalists to be on this trajectory. Further, when they do attend college, pure creationists and flexible creationists (i.e., creationists who allow for the possibility that God used evolution) both attend less selective colleges than naturalists, and pure creationists are less likely than naturalists to major in biology. These results suggest that evolution is a morally salient issue for many that influences their educational trajectories, highlighting the role that cultural schemas can play in shaping socioeconomic status.